Immunogenic clearance combined with PD-1 blockade elicits antitumor effect by promoting the recruitment and expansion of the effector memory-like CD8+ T cell - Seong A Kim; Seohyun Kim; Yeonsun Hong; Yoonjeong Choi; Yeji Lee; Minsu Kwon; Seung-Yoon Park; Cherlhyun Jeong; Gi-Hoon Nam; Rafael T. Han; In-San Kim (Translational Oncology)
Immune checkpoint inhibition shows promise for cancer treatment, but only a minority of patients respond. Combination strategies have been explored to overcome this resistance. Combining immunogenic clearance using immunogenic cell death inducers with a rho kinase inhibitor enhances phagocytosis of immunogenically dying cancer cells by antigen-presenting cells, stimulating tumor-specific immune responses by activating CD8+ T cells via dendritic cell-mediated priming. This approach increases the responsiveness of immune checkpoint blockade (ICB)-resistant cancer to ICB. However, the precise mechanisms remain unclear. This study elucidates cellular mechanisms of immunogenic clearance enhancing ICB response. Using single-cell RNA sequencing, we observed an increase in effector memory-like CD8+ T cells within the tumor microenvironment with combined treatment. We propose this cell cluster may originate from proliferating CD8+ T cells elevated by immunogenic clearance. Notably, abundant effector memory-like CD8+ T cells in ICB-responsive patients suggest their antitumor effect. Thus, increasing this cell population through enhanced T cell priming may improve the response of ICB-resistant tumors.